Akselerasi Mutu Pelayanan Program Studi Ilmu Hadits Menggunakan Metode QFD dan SWOT: Acceleration of Service Quality of Hadith Study Program Using QFD and SWOT Methods - Darussalam, Andi; Munadi, Radhie; D, A Zulfikar (Thawalib: Jurnal Kependidikan Islam, 2024)
This study aims to identify the attributes desired by students regarding proposed improvements to the quality of the Hadith study program at Alauddin State Islamic University of Makassar. The research method used is a mixed-methods approach. Data collection techniques include interviews (questionnaires), observations, and documentation. Data analysis involves tabulation, validity testing, and reliability testing. The research findings: Elements of good service quality that need to be maintained and improved include providing comfortable classrooms, consultation time with parents and lecturers, as well as support for underprivileged students. These improvement plans will serve as the basis for the program's policy, including the integration of digital systems, faculty training, and the addition of learning facilities. To address resistance to change, it is important to actively involve all parties and to socialize and implement changes gradually with management support. The Hadith program is committed to being the best through preparation for international accreditation and focusing on graduates' competitiveness in the global market.